EVALUASI KONSISTENSI PENULISAN DIAGNOSIS PADA RESUME MEDIS DAN RENCANA PULANG DALAM KETEPATAN KODE DIAGNOSIS INFEKSI DI RSUD DR. RASIDIN PADANG - Dewi Mardiawati; Rahmadhani Rahmadhani; Ghina Fadhila (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Inconsistencies in diagnosis writing and coding accuracy for infection cases remain common. Initial observation of 10 records at Dr. Rasidin Padang Hospital showed 60% inconsistency in diagnoses and 60% in coding. This study aimed to assess the consistency between medical summaries and discharge plans in relation to coding accuracy. Conducted from February to March 2025 using a descriptive quantitative method, the study involved 53 samples from a population of 114, selected via simple random sampling. Data were collected using a checklist and analyzed with univariate analysis via Computerisasi. Results showed 45.3% inconsistent diagnoses and 39.6% inaccurate codes. The issues were linked to suboptimal medical record completion by physicians and coders, affecting data quality and coding accuracy. Hospitals are encouraged to enhance supervision, guidance, and regular training to improve understanding of documentation and coding standards.Keywords: Consistency, Accuracy, Medical Summary, Discharge Planning